Immunohistochemical characteristics of molecular-biological subtypes of breast cancer - Marchuk, Irina N.; Smolyakova, Raisa M.; Shpadaruk, Ekaterina M. (Journal of the Belarusian State University. Ecology, 2020)
Breast cancer is a heterogeneous group of tumors that differ in morphology, clinical course and sensitivity to treatment. There are four molecular subtypes, each of which requires different treatment options, and has a different survival rate. During the immunohistochemical analysis, molecular subtypes of breast cancer were identified according to the levels of expression Her2 / neu, Ki-67, ER, PR, which must be considered to predict the course of the disease and the choice of treatment tactics for patients.